Malvinas Current at 40°S-41°S: First Assessment of Temperature and Salinity Temporal Variability - Paniagua, Guillermina Fernanda; Saraceno, Martin; Piola, Alberto Ricardo; Guerrero, Raul Alfredo; Provost, Christine; Ferrari, Ramiro; Lago, Loreley Selene; Artana, Camila Indira (Journal of Geophysical Research: Oceans)
The temporal variability of 11 months of in situ velocity, temperature, and salinity data collected at five moorings deployed at 40°S–41°S across the shelf-break in the Southwestern Atlantic is analyzed. Two distinct regimes characterized by strong and weak along-slope velocities are present. During the strong regime the Malvinas Current flows northward through the moorings while during the nearly 5 months long weak regime reversals of the along-slope velocities are frequently observed. Comparison with the previous in situ time series obtained in the same region shows that such an extended period of weak flow has not been previously observed. During the weak regime, Sub-Antarctic Mode Water is observed over the 1,800 m isobath at an average depth of 500 m. Water masses occupying the upper 1,600 m during the strong regime deepen and shift eastward during the weak period. Satellite geostrophic velocities and sea surface temperature clearly show that the weak regime is due to a deflection to the east of the Malvinas Current, upstream of the mooring position. Analysis of the vertical structure of the currents indicate that during the weak regime the flow weakens mostly at the surface and presents a very small vertical shear. In contrast, during the strong regime currents are surface-intensified. The change in the structure of the currents at the mooring location impacts the relationship between in situ and altimetry-derived currents: during the weak regime altimetry adequately represents (rmsd 12 cm/s) in situ currents in the whole water column, while during strong regime rmsd are larger than 15 cm/s below 600 m depth. Fil: Paniagua, Guillermina Fernanda. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Centro de Investigaciones del Mar y la Atmósfera. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Centro de Investigaciones del Mar y la Atmósfera; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y ...